2007
DOI: 10.1097/00004479-200701000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Is Patient Activation Associated With Outcomes of Care for Adults With Chronic Conditions?

Abstract: We examined the patient activation measure's (PAM's) association with process and health outcomes among adults with chronic conditions. Patients with high PAM scores were significantly more likely to perform self-management behaviors, use self-management services, and report high medication adherence, compared to patients with the lowest PAM scores. This population was 10 times more likely to report high patient-satisfaction scores, 5 times more likely to report high quality-of-life scores, and reported signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
339
11
11

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(376 citation statements)
references
References 11 publications
15
339
11
11
Order By: Relevance
“…eye examinations for people with diabetes, keeping diary of blood pressure readings), and control of chronic illness (e.g. HbA1c control, fewer hospitalizations) 13,14,[16][17][18][19][20] . Many of the studies are limited, however, by reliance upon self-reported health outcomes and use of relatively small samples.…”
Section: Introductionmentioning
confidence: 99%
“…eye examinations for people with diabetes, keeping diary of blood pressure readings), and control of chronic illness (e.g. HbA1c control, fewer hospitalizations) 13,14,[16][17][18][19][20] . Many of the studies are limited, however, by reliance upon self-reported health outcomes and use of relatively small samples.…”
Section: Introductionmentioning
confidence: 99%
“…Patient Activation is linked to health outcomes. 6 Physician skills such as participatory decision making can lead to improved patient activation and better outcomes. 7 Hibbard's Patient Activation Measure (PAM) has been shown to be a reliable measure, relatively easy to administer, and has been proposed as a health care quality measure.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, one may emphasize patient activation given links to greater self-management of mental illness in people with medical conditions (Mosen et al, 2006;Hibbard et al, 2007) as well as mental health conditions (Salyers et al, 2009;Green et al, 2010;Kukla et al, 2013). For example, Alexander et al (2012) noted that as little as establishing patient-physician relationships might help foster patient activation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of consumers with chronic conditions, including diabetes, asthma, heart failure, coronary artery disease, and chronic pain, Mosen et al (2006) found that higher patient activation was associated with better medication adherence, more involvement in selfmanagement services, and better quality of life and physical and mental functioning. Hibbard et al (2007) studied similar populations and found that the amount of self-management behaviors increased in consumers with high activation, and the change in behaviors lasted over time.…”
Section: Patient Activationmentioning
confidence: 99%